Desempenho e qualidade de carne de cordeiros em terminação suplementados com lisina e metionina protegidas - Muñeton, Lilian Paola Guevara (2020)
The correct balance of amino acids tends to increase the efficiency of the use of metabolizable protein for productive functions by animals, such as weight gain and milk production. In this sense, some authors propose the supply of diets with lower levels of crude protein (CP), since there is better efficiency in the use of nitrogen with less risk of excess supply. For this, amino acids known as limiting are supplement to animals, aiming to meet their demands, without reducing the CP content of the diet causing a negative impact on performance. In this sense, the present study was conduct with the objective of evaluating the effects of supplementation with lysine and methionine protected from the rumen associated with diets with CP reduction in relation to the requirements of the animals on the intake and digestibility of nutrients, productive performance and quality of the meat from stranded crossbreed lambs. Were used 34 crossbred lambs (Dorper × Santa Inês), distributed in completely randomized design. which were subject to the following experimental diets: T1 - 146 g CP/kg DM without supplementation with AAPR, T2 - 146 g CP/kg of DM of the diet with AAPR, T3 - 138 g CP/kg of DM of the diet with AAPR and T4 - 132 g of CP/kg of DM of the diet with supplementation with AAPR. The study was conduct for 42 days, during which data on intake and digestibility of nutrients, total and average daily weight gain, yield and carcass gain were obtain, as well as the meat quality of the animals after slaughter. The data were submitted to comparison of means by the tukey test (P <0.05) and contrasts between animals that were and were not supplemented with AAPR. There were no differences between experimental diets in terms of nutrient intake and digestibility, as well as in animal performance, with average values for DM intake and daily weight gain of 1.46 kg/d and 275 g, respectively. There were also no significant differences between treatments regarding the physical-chemical parameter of meat water-holding capacity (24.92 ± 0.85). A lower value (P <0.05) was observed for cooking weight loss for the meat of animals fed with the T3 diet (13.8% CP supplemented with AAPR). No differences were observed for diets with respect to L * and b * parameters, but for factor a * showed higher values for T1 (14.6% CP with AAPR). The shear force was affected by the diet offered, being lower in the T2 (14.6% CP with AAPR) and T4 (13.2% CP with AAPR) diets, but with no effect by supplementation with AAPR. The moisture and ash content were not modified by the diet, in contrast, in animals in which the CP content of the diet was reduced by 5% associated with supplementation with AAPR (T3) compared to the control, a higher fat content was found in beef. The decrease in CP content to 132 g of CP/kg DM with supplementation with AAPR did not negatively affect the performance of the animals and, thus, supplementation with AAPR allows reducing the CP content of the lamb diet by up to 10% in relation to the requirements. Supplementation with AAPR alters meat quality in diets with 13.8% CP. However, studies are need to assess amino acid requirements in lambs in the growing/finishing phase.